Technology‐based self‐monitoring system for on‐task behavior of students with disabilities: A quantitative meta‐analysis of single‐subject research. (30th December 2021) - Mize, Min; Park, Yujeong; Carter, Amanda
Abstract: Background: There have been several studies that involved technology‐based self‐monitoring procedures to increase on‐task behavior. Although there are continued advancements in technology application such as functions that are embedded in the application (e.g., reinforcement, feedback), the appropriate use of technology is required to be accompanied by evidence‐based guidance. Objectives: The purpose of this meta‐analytic approach was to (a) examine the effectiveness of a technology‐based self‐monitoring system on the on‐task behavior of students with disabilities and (b) provide information that can support the use of a technology‐based approach as an effective method for the teaching of relevant behavioral skills. Methods: All reviewed 16 studies employed a single‐case research design, targeting technology‐based self‐monitoring interventions for students with disabilities. Studies were descriptively analyzed and evaluated for methodological quality using the What Works Clearinghouse (WWC) standards and criteria. Additionally, to examine the level and trend of reading fluency outcomes, Tau‐ U was calculated across the studies by measuring the impact of various moderator variables on the intervention effects. Results and Conclusions: Overall, studies showed a strong effect of using the technology‐based self‐monitoring on on‐task behaviors. The impacts of six possible moderator variables (i.e., school level, types of technology, student training, teacher feedback and teacher reinforcement) were analyzed and there was no significant difference in the six variables with regards to the effects of the technology‐based self‐monitoring on the improvement of on‐task behaviors. Implications: Based on the findings that support the positive impact of using mobile technology for increasing on‐task behaviors of students with disabilities, directions for future research and practical applications were discussed. Lay Description: The appropriate use of technology‐based self‐monitoring intervention for on‐task behavior needs to be accompanied by evidence‐based guidance, which could be done by evaluating its effectiveness. All interventions in the reviewed studies included portable mobile technology from handheld devices (to collect student response) to the most recent iPad device. The overall effect size indicated a very large positive effect when using technology‐based self‐monitoring interventions on improving on‐task behaviors. The portability of mobile technology (e.g., iPad, iPod, or a handheld computer in early 2000s) made it possible for students with disabilities to use the technology frequently and students with disabilities were able to do so with ease.